Примена на balanced scorecard системот за управување на организациските перформанси во високото образование во Р. Македонија - Ефтимов, Љупчо (Економски факултет, УКИМ, Скопје, 2012)
In the last two decades, European higher education institutions have faced many challenges: reduced financial support for higher education, encouraged competition by allowing free entry of foreign universitites and establishment of private universities, constant pressures for greater financial autonomy and demands for their restructuring and reforms. In this direction special attention deserve reforms as a result of the adoption of the Bologna Declaration in 1999. Its main goal is building a unified European educational system by introducing similar, comparable and compatible higher education quality standards and harmonization of the duration of the academic cycles in almost all countries in Europe. The challenges that faced Macedonian higher education institutions in the process of implementing the Bologna principles and reforms in order to achieve better quality, were not easy or naive. Based on a survey of 981 students from public and private universities in Macedonia about their opinion for the situation in Macedonian higher education, we managed to detect the basic problems, challenges, and key areas for further reforms and improvements in Macedonian higher education. Such changes undoubtedly require more responsibility and real managerial behavior, far different from former collegial or confirmative management. The only way for fast adjustment of the universities to the new competitive conditions is to explore all possibilities for effective implementation of some of the most popular management concepts and business techniques such as Balanced Scorecard system. Implementing a strategic management system, such as the Balanced Scorecard, provides an approach for successfully leading change through strategy design, implementation, measurement, and feedback. Although the application of the balanced scorecard (BSC) in the business sector is well documented, very little research has been reported regarding the adaptation or application of the BSC in the education sector. For this purpose, relied on analysis of existing BSC-related literature and reported results and experiences from its implementation in business, first, we tried to propose a suitable process for creating a Balanced Scorecard system for higher education institutions, and then we design a specific BSC system for the Faculty of Economics-Skopje, University Ss. Cyril and Methodius, easily adaptable for implementation in other Macedonian higher education institutions. The proposed Balanced Scorecard system should increase efficiency and university performance in achieving their strategic goals. Also it can be used to communicate and build a common understanding of institutional vision and strategy, to guide faculty and staff toward common goals, and to identify areas where improvements are needed.
Employment of the balanced scorecard performance management system in the higher education in Republic of Macedonia
Докторска дисертација одбранета во 2012 година на Економскиот факултет во Скопје, под менторство на проф. д–р Димитар Бојаџиоски.
Keywords: higher education, higher education institutions, reforms, performance measurement, performance management, Balanced Scorecard (BSC), Balanced Scorecard model